Comparison of Effectiveness of Hydrotherapy and Amitriptyline in Fibromyalgia Treatment - Hilal Kocabaş,; Gamze Yılmaz,; Hatice Uğurlu, (Archives of Rheumatology, 2007)
Objective: Fibromyalgia (FM) is a nonarticular rheumatic disorder with an unknown etiology which is characterized by diffuse musculoskeletal pain, tenderness on specific anatomical points and psychological discomfort. There isn't any standardized treatment regime. In recent years some nonpharmacological applications have been come in prominence. These are, hydrotherapy, balneotherapy and massage. In this study, we compared effectiveness and side effects of amitriptyline and hydrotherapy which were used in the treatment of fibromyalgia. Patients and Methods: A total of 51 female patients with FM were included. They were randomly divided into two groups. Group 1 (n=20) took 15 session hydrotherapy along three weeks, group 2 took (n=31) 10 mg/day amitriptyline for eigth weeks. Both groups were examined at the beginning and at the end of the treatment, third and sixth month. The number of tender points (NTP) were evaluated by digital pressure. Likert scoring system were used to assess pain intensity, morning stiffness, skin sensitivity, sleep disturbances, fatigue and muscle spasm. Hamilton Depression Scale (HDRS) and Fibromyalgia Impact Questionnaire (FIQ) were used to evaluate psychologic condition and physical and functional capacity, respectively. Results: In group 2, significant improvement was found in pain, sleep disturbance, fatigue, NTP, FIQ and HDRS values at the end of the treatment. In group 1 significant improvement was obtained in all measurements except skin sensitivity and HDRS. This improvement prolonged up to 3 months in pain, morning stiffness, fatigue, NTP and FIQ. When the two groups were compared there was a significant improvement in hydrotherapy group in pain, sleep disturbance and FIQ at the end of the treatment. Conclusion: Effectiveness of hydrotherapy is more and longer than amitriptyline. When the adverse effects of tricyclic antidepressants are considered, it will be useful to prefer any regimen which has no advers effect. (Rheumatism 2007; 22: 91-6)